2017
DOI: 10.1061/(asce)ei.1943-5541.0000321
|View full text |Cite
|
Sign up to set email alerts
|

Insolvency of Small Civil Engineering Firms: Critical Strategic Factors

Abstract: Construction industry insolvency studies have failed to stem the industry's high insolvency tide because many focus on big civil engineering firms (CEF) when over 90% firms in the industry are small or micro (S&M). This study thus set out to uncover insolvency criteria of S&M CEFs and the underlying factors using mixed methods. Using convenience sampling, storytelling

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…This analysis technique was chosen as it thrives in identifying the unexplained variables that impact the covariation between many data. These variables describe underlying ideas that are difficult to capture with a single variable (Doloi et al , 2012; Kline, 2014; Alaka et al , 2017). The research methodology flowchart is as shown in Figure 1 below:…”
Section: Methodsmentioning
confidence: 99%
“…This analysis technique was chosen as it thrives in identifying the unexplained variables that impact the covariation between many data. These variables describe underlying ideas that are difficult to capture with a single variable (Doloi et al , 2012; Kline, 2014; Alaka et al , 2017). The research methodology flowchart is as shown in Figure 1 below:…”
Section: Methodsmentioning
confidence: 99%
“…It is not surprising to see working capital/ total assets as the chief contributor since it has to do with liquidity of the firm. Construction firms are known to always need high liquidity if they are to keep their projects running [29,48,68,69]. Poor liquidity is what led to the recent failure of Carilion construction firm in the United Kingdom.…”
Section: The Models and The Resultsmentioning
confidence: 99%
“…Construction management can be complex, as it involves multiple contracts, and mistakes can have costly implications. AI can diminish the risk of human errors by automating the efforts of contract managers to ensure that processes are faster and more accurate [59].…”
Section: Construction Contractsmentioning
confidence: 99%
“…Clash detection: Clash detection is essential in the design phase and needs to be simplified and accelerated by AI. Technologies such as BuildingSP and GenMEP are in development, which detects clashes in real-time without the need to export files to other platforms [59].…”
Section: Design Phasementioning
confidence: 99%